Sustainable Economy from Equity Mutual Fund Characteristic and Performance: Indonesia within 2017-2022 - Wijaya, Chandra Purnama; Wahyudi, Sugeng (LifeSciFi, 2024)
Sustainable economy become trending in past few years. It’s about economic activity that will bring long term positive impact without causing any negative effect for anyone. Doing sustainable business practices can be implemented by investment. Mutual fund is one type of investment instrument in Indonesia. Mutual fund can be prepared to face sustainable economy in the future. Equity mutual fund in Indonesia within 2017 – 2022 has the most volatile NAV/UNIT. From the Mutual fund Performance, it can be known whether a mutual fund is good or not and it will represent the sustainable economy of mutual fund investment. Using a purposive sampling method there are 80 Indonesian equity mutual funds from 2017-2022. The analysis techniques used was panel data regression using the e-views version 12 application. The result from the research is that tenure and stock selection have a significant positive effect. Portfolio turnover and fund size have a significant negative effect. Market timing does not have a significant effect. If all the characteristic could give significant positive effect, it will rise the mutual fund performance so it will bring sustainable economy for Indonesia.